JBI's approach to evidence implementation: a 7-phase process model to support and guide getting evidence into practice. Issue 1 (22nd March 2023) - Porritt, Kylie; McArthur, Alexa; Lockwood, Craig; Munn, Zachary
Abstract : ABSTRACT: In this paper, we provide an overview of JBI's approach to evidence implementation and describe the supporting process model that aligns with this approach. The central tenets of JBI's approach to implementing evidence into practice include the use of evidence-based audit and feedback, identification of the context in which evidence is being implemented, facilitation of any change, and an evaluation process. A pragmatic and practical seven-phased approach is outlined to assist with the 'planning' and 'doing' of getting evidence into practice, focusing on clinicians as change agents for implementing evidence in clinical and policy settings. Further research and development is required to formally evaluate the robustness of the approach to better understand the complex nature of evidence implementation.